Studies of Marine Sulfated Polymannuroguluronate on Endothelial Cell Proliferation and Endothelial Immunity and Related Mechanisms - Lichun Wang; Meiyu Geng; Jing Li; Huashi Guan; Jian Ding (Elsevier, 2003)
Anti-proliferation action and enhancement of endothelial cell immunity and related mechanisms by marine sulfated polymannuroguluronate (SPMG) were investigated in the present studies. Endothelial cell proliferation was evaluated by MTT assay. Intercellular adhesion molecule-1 (ICAM-1) expression was analyzed by flow cytometry. The interaction of SPMG with basic fibroblast growth factor (bFGF) was evaluated by surface plasmon resonance. Results showed that SPMG exhibited a significant inhibitory effect against proliferation in both normal human umbilical vein endothelial cells (HUVEC) and bFGF-treated HUVEC, the action of which was completely abrogated by bFGF antibody. SPMG exerted high affinity to bFGF in a multivalent pattern, characterized by one molecule SPMG binding to 3 - 4 molecules of bFGF. Moreover, SPMG enhanced ICAM-1 expression in HUVEC and prevented and restored bFGF-treated downregulation of ICAM-1 expression in HUVEC, the expression of which was not counteracted by bFGF antibody. In conclusion, this is the first report demonstrating that SPMG exerted an anti-proliferation effect dependent on the bFGF-regulated pathway and afforded upregulatory activity on ICAM-1 expression regardless of the involvement of bFGF.